2002
DOI: 10.1053/jhep.2002.35820
|View full text |Cite
|
Sign up to set email alerts
|

The significance of human jagged 1 mutations detected in severe cases of extrahepatic biliary atresia

Abstract: Mutations of human jagged 1 (JAG1) gene are responsible for Alagille Syndrome (AGS), whose 2 main symptoms are intrahepatic bile duct hypoplasia and pulmonary stenosis. We examined the JAG1 mutation in extrahepatic biliary atresia (EHBA), which is similar in phenotype to AGS, although a different pathogenesis is suggested. In 102 cases of EHBA, 9 missense mutations were detected, including 2 intrafamilial expressions in the propositus and an aunt of one family. These mutations were all missense and sporadic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 37 publications
0
40
1
Order By: Relevance
“…Kohsaka et al found JAG1 mutations in 9 of 102 patients with BA, and these patients appeared to have more severe disease. 32 Because of the association between BA and laterality defects, 5 investigators have examined patients with BA for mutations in genes involved in left/right sidedness. No mutations in INV were identified in 7 patients with BA, 7 whereas CFC1 mutations were found in 5 of 10 patients with BA and laterality defects, 33 although the significance of these mutations is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Kohsaka et al found JAG1 mutations in 9 of 102 patients with BA, and these patients appeared to have more severe disease. 32 Because of the association between BA and laterality defects, 5 investigators have examined patients with BA for mutations in genes involved in left/right sidedness. No mutations in INV were identified in 7 patients with BA, 7 whereas CFC1 mutations were found in 5 of 10 patients with BA and laterality defects, 33 although the significance of these mutations is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Huh-7 cells seeded in a 24-well plate at 2 · 10 4 cells per well in DMEM complete medium and cultured overnight were washed twice with PBS, starved for 5 h in DMEM medium containing 0.5% FBS and treated with 20 ng/mL TNFa (R&D Systems, Minneapolis, MN, USA) to induce IL-8 expression [23]. Cells were grown for an additional 18 h in the presence or absence of 200 lm thalidomide, 10 lm wedelolactone or 13 nm NAI-1.…”
Section: Inhibition Of Il-8 Expression By Thalidomide and Nf-jb Inhibmentioning
confidence: 99%
“…Thalidomide is reported to reduce TNFa-induced IL-8 levels in endometriotic stromal cells [27]. To validate that thalidomide acts similarly in Huh-7 hepatoma cells to inhibit TNFa induction of IL-8 expression [23], exogenous TNFa was added to Huh-7 cell cultures grown in the presence or absence of thalidomide. As thalidomide was reported to inhibit cytokine synthesis by blocking IKK, we also used the IKK-specific inhibitors wedelolactone and NAI-1 that were expected to mimic the action of thalidomide on IKK and thus block IL-8 expression [12].…”
Section: Thalidomide and Ikk Inhibitors Block Il-8 Protein Synthesis mentioning
confidence: 99%
“…We previously showed that common variants with footprints of genetic-environmental interaction confer risk of BA. Also, a handful of rare mutations has been detected in syndromic BA or non-syndromic BA with severe clinical manifestations [37]. Overall, BA represents a rare disease with a complex genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Although exploration on the developmental candidate gene mutation in BA was fruitful, its value is limited as individual finding that may represent only a heterogeneous group of patients [57]. …”
Section: Introductionmentioning
confidence: 99%